Comprehensive analyses of 723 transcriptomes enhance genetic and biological interpretations for complex traits in cattle - Fang, Lingzhao; Cai, Wentao; Liu, Shuli; Canela-Xandri, Oriol; Gao, Yahui; Jiang, Jicai; Rawlik, Konrad; Li, Bingjie; Schroeder, Steven G.; Rosen, Benjamin D.; Li, Cong-jun; Sonstegard, Tad S.; et al. (Genome Research, 2020)
By uniformly analyzing 723 RNA-seq data from 91 tissues and cell types, we built a comprehensive gene atlas and studied tissue specificity of genes in cattle. We demonstrated that tissue-specific genes significantly reflected the tissue-relevant biology, showing distinct promoter methylation and evolution patterns (e.g., brain-specific genes evolve slowest, whereas testis-specific genes evolve fastest). Through integrative analyses of those tissue-specific genes with large-scale genome-wide association studies, we detected relevant tissues/cell types and candidate genes for 45 economically important traits in cattle, including blood/immune system (e.g., CCDC88C) for male fertility, brain (e.g., TRIM46 and RAB6A) for milk production, and multiple growth-related tissues (e.g., FGF6 and CCND2) for body conformation. We validated these findings by using epigenomic data across major somatic tissues and sperm. Collectively, our findings provided novel insights into the genetic and biological mechanisms underlying complex traits in cattle, and our transcriptome atlas can serve as a primary source for biological interpretation, functional validation, studies of adaptive evolution, and genomic improvement in livestock.
10.1101/gr.250704.119